Opaqueness to the light of understanding: an investigation into some of the difficulties experienced by a sample of Transkeian matriculants with the components of the concept of chemical equilibrium - Mammen, Kuttickattu John (Rhodes University, Faculty of Education, Department of Education, 1992)
The purpose of the study was to collect and collate information pertaining to common misconceptions of components of the concept of chemical equilibrium amongst a sample of Transkeian matriculants. 'Equilibrium' is a fundamental concept in physics and chemistry and 'chemical equilibrium' is an important chemistry topic in both the higher grade and standard grade South African matriculation physical science syllabuses. In recent years, South African teachers have identified chemical equilibrium as the most difficult section of the matric physical science syllabus for both teachers and pupils. It has been shown that teachers themselves lack understanding of the basic concepts underlying chemical equilibrium. Constructivist learning theories arise out of research in cognitive psychology. These theories conceive of cognitive development as the assimilation and accommodation of new ideas into extant, dynamic cognitive structures. An inference from the theories is that a study of the preconceptions and/or misconceptions held by pupils before they are exposed to instruction would enable teachers to avoid generating or reinforcing misconceptions. Hence teachers could also take deliberate steps to eradicate those already existing. The sample consisted of 112 Transkeian matriculants from four government senior secondary schools in the Southern Transkei. All were taking physical science. The test consisted of a 40 item multiple choice battery. Each question had three distracters and the options were randomized to avoid patterns and hence guessing. Questions dealing with closely associated concepts were grouped in the paper but no indication of this was given in the paper. The questions are analyzed singly. A brief introduction and outline of the theory on which the group of questions was based is given in each case. The analysis makes use of the frequency of choice of all options, discrimination indices, although they were generally low and item difficulties. The intent in each analysis is to identify the possible misconception(s) underlying wrong answers. Finally conclusions based on the discussion are drawn and recommendations for teaching and further research made.
Keywords: Chemical equilibrium; Physical sciences -- Study and teaching (Secondary) -- South Africa -- Transkei; Black people -- Education -- South Africa